2011
DOI: 10.1128/jcm.02628-10
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Capsular Genes of Streptococcus pneumoniae Serotype 6A, 6B, 6C, and 6D Isolates

Abstract: Recently, Streptococcus pneumoniae serotypes 6C and 6D have been identified. It is thought that they emerged by the replacement of wciN ␤ in the capsular loci of serotypes 6A and 6B, respectively. However, their evolution has not been unveiled yet. To investigate the evolution of four serotypes of S. pneumoniae serogroup 6, four genes of the capsular polysaccharide synthesis (cps) locus, wchA, wciN, wciO, and wciP, of isolates of S. pneumoniae serotypes 6A, 6B, 6C, and 6D were sequenced. Multilocus sequence ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
26
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 14 publications
7
26
0
1
Order By: Relevance
“…Bratcher et al (5) proposed that serotype 6C has been produced by introduction of a DNA fragment spanning the capsular polysaccharide synthesis (cps) locus irrespective of serotypes 6A and serotype 6D has resulted from a recombination between the cps loci of serotypes 6B and 6C. In addition, we also showed the emergence of cps loci of serotypes 6C and 6D by complicated recombination (23).…”
supporting
confidence: 54%
See 3 more Smart Citations
“…Bratcher et al (5) proposed that serotype 6C has been produced by introduction of a DNA fragment spanning the capsular polysaccharide synthesis (cps) locus irrespective of serotypes 6A and serotype 6D has resulted from a recombination between the cps loci of serotypes 6B and 6C. In addition, we also showed the emergence of cps loci of serotypes 6C and 6D by complicated recombination (23).…”
supporting
confidence: 54%
“…pneumoniae serotype 6D isolates have been found in several countries and are relatively abundant in South Korea (8,23). In our study, two main clones (ST282 and ST3171) have been identified among S. pneumoniae serotype 6D isolates from Korea.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…n a previous study, we identified a distinct group, group 6X, among serogroup 6 Streptococcus pneumoniae isolates (1). These group 6X strains were hypothesized to be similar to class 2 isolates in previous reports (2,3) and capsular subtype 6B-III in a study by Elberse et al (4).…”
mentioning
confidence: 59%